2020
DOI: 10.3390/e22020172
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Entropies in the Spanish Football League: A Network Science Perspective

Abstract: We quantified the spatial and temporal entropy related to football teams and their players by means of a pass-based interaction. First, we calculated the spatial entropy associated to the positions of all passes made by a football team during a match, obtaining a spatial entropy ranking of Spanish teams during the 2017/2018 season. Second, we investigated how the player’s average location in the field is related to the amount of entropy of his passes. Next, we constructed the temporal passing networks of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…In the last decade, there has been a plethora of research describing and analyzing the match performance data from soccer World Cups using several approaches such as multivariate analyses and machine learning [1][2][3][4][11][12][13][14][15], passing networks based on space, time and the multilayer nature of the game [16] or based on spatial and temporal entropy related to football teams and their players by means of a pass-based interaction [17] and social network analyzes to study the interaction between a player and their teammates (for example a ball passing network) through graph theory to assess the structural and topographical characteristics of personal interactions between team members [18]. This type of descriptive research provides important information that can be used to improve training and adapt tactics, however analyses, such as machine learning, can identify performance indicators, whether physical or technical that may predict what will occur during the match [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there has been a plethora of research describing and analyzing the match performance data from soccer World Cups using several approaches such as multivariate analyses and machine learning [1][2][3][4][11][12][13][14][15], passing networks based on space, time and the multilayer nature of the game [16] or based on spatial and temporal entropy related to football teams and their players by means of a pass-based interaction [17] and social network analyzes to study the interaction between a player and their teammates (for example a ball passing network) through graph theory to assess the structural and topographical characteristics of personal interactions between team members [18]. This type of descriptive research provides important information that can be used to improve training and adapt tactics, however analyses, such as machine learning, can identify performance indicators, whether physical or technical that may predict what will occur during the match [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…But the existing structural entropy model has no quantitative method for the uncertainty of the results [46,47]. In addition, there are many other fields of complexity evaluation based on information entropy, such as a stock network [50], a brain network [51], the spatial and temporal entropy of a football game [52], and species distribution [53]. The uncertainty of their calculation results originates from the uncertainty of test data, that was, the uncertainty of information.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Real Madrid's unpredictability in passing may have increased the chances of goal-scoring opportunities, potentially having contributed to the win. The concept of entropy to model social interactions has already been used [26][27][28]. Newman and Vilenchik (2019) used the concept of relative entropy to model the interactions of players passing the ball in football, having found that when comparing two opposing teams, higher entropy values lead to more chances of creating goal-scoring opportunities [27].…”
Section: A Case Studymentioning
confidence: 99%